The Significance of Insulin Resistance in Nondiabetic Breast Cancer Patients - Kundaktepe, Berrin Papila; Durmus, Sinem; Cengiz, Mahir; Kundaktepe, Fatih Orkun; Sozer, Volkan; Papila, Cigdem; Gelisgen, Remise; Uzun, Hafize (ELMER PRESS INC, 2021)
Background: The relationship between insulin resistance (IR) and prognostic factors in breast cancer (BC) in premenopausal (pre-M) and postmenopausal (post-M) women is still controversial. We evaluated the potential association between hemoglobin A1c (HbA1c), fasting blood glucose (FBG), fasting insulin levels (FILs), the homeostasis model assessment index (HOMA), and the prognostic factors of BC in nondiabetic patients with pre-M and post-M breast tumors. Methods: We compared 80 nondiabetic patients with pre-M and post-M breast tumors to 60 women with normal mammography as a control. Results: Age, body mass index (BMI), FBG, and HbA1c did not differ between the groups. FIL (P < 0.001) and HOMA-IR (P < 0.001) of the BC group were significantly higher than in the control group. FIL (P < 0.001) and HOMA-IR (P < 0.001) of the BC group were significantly higher than in the control group, for both pre- and postM patients. FIL and HOMA-IR values were found to be significantly higher in the patients with stage IV BC than in other stages of BC. FIL and HOMA-IR are highly specific and sensitive parameters in their ability to diagnose BC. Conclusions: FIL and HOMA-IR are associated with BC risk in nondiabetic patients with pre-M and post-M breast tumors. When BC risk was evaluated according to the stage of menopause, no difference was observed; only the disease stage was significant. FIL and IR may function as potential biomarkers and therapeutic targets for human cancers.
Keywords: Breast cancer; HbA1c; Fasting blood glucose; Fasting insulin; Insulin resistance; GROWTH-FACTOR-I; HORMONE-BINDING GLOBULIN; GLUCOSE-METABOLISM; IGF-I; RISK; PREMENOPAUSAL; PROTEIN-1; OBESITY; CELLS; Endocrinology & Metabolism